Development and content validation of the Multifactoral assessment of perceived social support (MAPSS), a brief, patient-reported measure of social support for use in HIV care. (18th December 2019) - Fredericksen, Rob J.; Fitzsimmons, Emma; Gibbons, Laura E.; Dougherty, Sarah; Loo, Stephanie; Shurbaji, Sally; Batey, David S.; Avendano-Soto, Sonia; Mathews, William C.; Christopoulos, Katerina; Mayer, Kenneth H.; Mugavero, Michael J.; et al.
ABSTRACT: Low perceived social support (SS) negatively impacts health outcomes. We developed a measure of perceived SS for use in HIV care. We sought and categorized legacy items, selecting strongest items within categories. We elicited SS concepts from patients in English/Spanish, coded transcripts to match item pool content, and developed new items for salient unrepresented content. In focus groups, patients prioritized highly-matched items. We conducted cognitive interviews on high-priority items, and validity testing on final items against two legacy measures. From interviews ( n = 32), we matched the following concepts: sense of belonging/inclusion; communication; emotional support; feeling accepted by others as a person; companionship; and practical support. We identified a new concept: support from friends/family in remaining healthy. Focus groups ( n = 23) prioritized emotional support, communication, and support to remain healthy. Cognitive interviews ( n = 30) found items were well-understood. The final 8-item measure performed well with patients ( n = 708), with good construct validity. We used an Item Response Theory program to create a 3-item Short Form version of the measure, which captures 96% of patients indicating low social support. We developed the Multifactoral Assessment of Perceived Social Support (MAPSS) and Short Form (MAPSS-SF); brief, clinically relevant, sufficiently unidimensional measures of SS for use in HIV care.